До питання щодо оцінки впливу режиму експлуатації Київської ГЄС на концентрацію стронцію-90 на витоку з Київського водосховища - Sizonenko V.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2000)
The model takes into consideration both the water transportation time and Sr-90 contamination through the reservoir. As a result, the model UNDBE considerably increases the accuracy of prediction of Sr-90 concentration in the reservoir outflow particularly in the case of a short time forecast. This approach does not require more detailed field measures than the full mixed camera model does. The mathematical and soft complexity of the model has increased insignificantly. There are results of modeling the Sr-90 concentration in the Kiev reservoir after the Chernobyl accident in the article. With aid of the model the influence of the modes of the Kiev HHP operation on the concentration change has been evaluated.